Strike-slip salt tectonics in the Shuntuoguole Low Uplift, Tarim Basin, and the significance to petroleum exploration. (May 2022) - Bian, Qing; Deng, Shang; Lin, Huixi; Han, Jun
Abstract: The connection between source rock and reservoir separated by salt strata is a global problem. Taking Tarim Basin as a typical case, this paper studies how the No. 5 strike-slip fault passes through the salt layers. The No. 5 strike-slip fault system in the Shuntuoguole Low Uplift in the Tarim Basin, China, interacts with Cambrian salt layers at depth. In the present study, a part of this fault system was investigated to assess structural characteristics of the Yijianfang (Ordovician carbonate layer) and the Wusonggeer (Cambrian salt layer) formations. Seismic data reveal three structural styles in the salt layer including transpression, transtension, and pure strike-slip. In transpressional segments, the salt layer is thinned accross the fault plane; transtensional segments involve minor reactive salt diapirs, and pure strike-slip segments display no noticeable variation in the salt thickness. The impact of the deep strike-slip salt tectonics on petroleum exploration in the area is discussed using data from seven wells. Wells in transpressional segments, where the salt is thin, are characterized by good production, whereas those in transtensional segments, where the salt is thick, exhibit poor production. The salt prevents the migration of oil and gas along the strike-slip fault. Strike-slip salt structures examined in the present study improve the understanding of the associated tectonics in the central Tarim Basin and provide insights on hydrocarbon migration and accumulation in the basin. Highlights: This paper summarizes research on strike-slip salt tectonics in the Shuntuoguole Uplift, Tarim Basin. In transpressional segments, the salt layer is tectonically thinned and exhibits an x-shape; transtensional segments involve minor reactive salt diapirs, and pure strike-slip segments display no conspicuous variation in the salt thickness. Wells in transpressional segments, where the salt is thin, are characterized by good production, whereas those in transtensional segments, where the salt is thick, exhibit poor production.